Cracking the GRE : (Penguin Random House, 2017)
THE PRINCETON REVIEW GETS RESULTS. Get all the prep you need for a perfect score on the Quantitative and Verbal sections of the GRE with 4 full-length practice tests, thorough GRE topic reviews, and extra practice online.